EKSISTENSI AKKAWARU, UPACARA ADAT KEPERCAYAAN DI BUTTA TOA KABUPATEN BANTAENG - Fifie Febryanti Sukman (Universitas Andalas, 2018)
Belief in traditional ceremony can not be separated in a community system. The existence now serves as a tool for people to engage in activities related to various beliefs or religions. The purpose of this research is to know Akkawaru ceremonial procession procession in Bantaeng Regency, South Sulawesi. This research uses a qualitative method. Data collection techniques in this research consisted of direct observation and in-depth interviews. Data analysis technique used is an interactive analysis model that includes four components of data collection, data reduction, data presentation and conclusion. Based on the results of research that has been done can be concluded Akkawaru is a ceremony of customs to reject the reinforcement has become one of custom trust that can not be separated from community life in Bantaeng Regency. Keywords: traditional ceremony, Akkawaru, Butta Toa